British Converts to Islam, Habitus and Social Positioning - Sealy, Thomas (Journal of Muslim minority affairs, 2021)
The number of people converting to Islam in Europe has been growing in recent years and interest in this phenomenon has gained increasing attention. Scholarly attention has sought in particular to “locate” converts in relation to majority and minorities in society. One way of conceiving and theorising in this vein has been to focus on the notion of habitus, with alternative emphases of change or continuity. This article engages with conversion seen through the lens of habitus through a focus on converts to Islam in Britain. The article argues that these focuses on habitus over-emphasise practice against faith or belief and emphasise change against continuity or vice-versa. The article argues that what we need to focus on is the dynamic process between change and continuity found in the negotiations converts make as they seek to navigate their sense of self and social relations. Moreover, the article suggests that an emphasis on practice against faith or belief distorts how we understand these negotiations and the subsequent ways in which converts to Islam in Britain position themselves in relation to “majority society” and Muslim communities.